LINGUODIDACTIC ISSUES OF FOREIGN LANGUAGE TEACHING IN THE CONTINUING EDUCATION SYSTEM (Journal of Universal Science Research, 2025)
This article explores the linguodidactic aspects of foreign language teaching within the continuing education system. It highlights the importance of adaptive teaching methods, learner-centered approaches, and the integration of modern technologies to address the diverse needs of adult learners. The discussion focuses on the theoretical foundations of linguodidactics, challenges in curriculum development, and the significance of lifelong learning in a globalized world. Special attention is given to methods that enhance motivation, intercultural competence, and communicative skills in non-traditional learning environments.